Genetic sibship and parental reconstruction shed light on the mating systems and larval dispersal of an iconic Australian freshwater fish - J. E. O'Dwyer; K. A. Harrisson; Z. Tonkin; J. Lyon; B. Zampatti; W. Koster; S. Raymond; D. Dawson; C. Bice; N. Murphy (Journal of Fish Biology, 2026)
Mating systems shape the population dynamics of species, influencing attributes such as effective population size and population persistence. Traditionally, genetic analysis of mating systems includes the genotyping of putative parents to determine parentage. However, for cryptic or migratory species, and those with large populations, comprehensive sampling of adults is often not feasible. One underutilised alternative is to reconstruct parental genotypes from sibling relationships (i.e., sibship). We develop a generalisable sibship workflow for delineating types of first‐ and second‐ order kinship classifications in medium‐/low‐density SNP marker datasets and apply it to investigate the mating systems of the iconic Australian freshwater fish, Murray cod ( Maccullochella peelii ) using larvae collected over five breeding seasons and three breeding locations. We explored the relative occurrences of monogamous and polygamous pairings within and across breeding seasons along with larval dispersal patterns, and connectivity among breeding locations. Whilst monogamy was the most common mating strategy identified within each breeding season, only a single instance of multi‐year pair‐bonding was detected. Across seasons, 18% of putative adults were redetected and bred with a new partner, and within‐season polygynandry was detected in all three study reaches. Larval kin were found up to 71 km apart over only a few weeks of sampling and kin pairs were detected across two of the breeding locations (120–150 km apart) over seasons. Relatively high rates of polygynandry in wild Murray cod may promote the maintenance of genetic diversity and reduce vulnerability to recruitment disruptions in a climatically variable river system. Our study provides a valuable case study demonstrating that sibship analysis can provide insights into mating systems and dispersal potential of species where sampling adults is logistically difficult compared with collecting offspring.